Saídi: um estudo sobre a espetacularidade, história e memória da dança tradicional do Egito - SILVA, Anicèe do Carmo e (2023)
This course completion work was organized in accordance with Normative Instruction No. 01/2022- PROEG/UFPA, which provides, in an exceptional and temporary way, on the academic guidelines for the standardization and realization of the Final Paper, making its way of elaboration and presentation more flexible , due to the consequences resulting from the COVID- 19 pandemic, in accordance with Art. 4, which in paragraph I refers to the elaboration of a scientific text in the form of an expanded abstract; II – presentation of work at a technical- scientific event, with certification and IX – report on special projects. In this sense, I present the report of the Institutional Program of Scholarships for Initiation to Artistic Production – PIBIPA/ICA/UFPA for the year 2020/2021, in which I was a scholarship holder, by the Research Project Dance and Ethnocenology, of the Faculty of Dance of UFPA, with the research entitled Saídi: A study on the Spectacularity, History and Memory of Traditional Egyptian Dance, which resulted in the creation of a documentary video. The research unfolded in an Expanded Summary called Raks al Assaya: the spectacularity of the female body in Saídi dance in contemporary times, communicated at the XIII International Seminar on Dance Research at UFPA. For this, I used as a theoretical and methodological reference the studies of Ethnocenology, through the authors Pradier (1995), Bião (1996) and Amoroso (2009) and on the Arab dances Leão (2020) and Mahaila (2016). The research was defined as research with a qualitative approach, through the ethnocenological bias. Having as main objective studies, bibliographical research on the culture, dance and folklore of the Arab countries, on Belly Dance, Ethnocenology and Orientalism. I emphasize that as a practitioner and teacher of Arabic dances, the research increased my knowledge framework to teach classes based on historical knowledge and not only practical, but, mainly, with a theoretical-scientific reference, thus providing a better understanding of the culture and traditions of the Arab people.